Processos produtivos e trabalho-educação: a incorporação do caboclo catarinense na indústria madeireira - Martendal, Jose Ari Celso (1980)
The object theme of the present study is a population of caboclos that absorbed as manual workers in the saw-mills which were mounted in the highland region of Santa Catarina since 1950. The abundance of araucaria (native kind of pine) the opening of markets, and the corroboration of other industrial exploration conditions encouraged a great crowd of small en.- trepreneurs, coming basically from the state of Rio Grande do Sul, to migrate and settle down, building up a lot of saw-mills near rich forests and fields. The saw-mills started aprosperous production of timber sawn in planks. The process of industriali zation was so intensive, the destruction of pine woods soviolent that, in less than three decades, the forests ran out of tree reserves. The caboclos, absorbed as manual workers in production of timber, lived traditionally in an system of subsistense, either from the cultivation of pine the economic their land (planter caboclo) or as labourers in cattle-growing farms (farm hand caboclos). Nevertheless, the 'advantages' that were offered them by the new-comer entrepreneurs (a salary paid in money, a new house in a village, and other favours) helped the great majority of caboclos to abandon their traditional work and enlist as 'workmen' in saw-mills. The new job, besides being a novelty, was an opportunity for a change in status. Subsequently, the running out of forests of araucaria and the resultant progressive shut-down of saw-mills caused the crowd of workmen to be out of imployment and to form to form a migratory flood toward the most important town of the region, Lages. The town of Lages, however, having made of the timber i ts main economic support wi thout the implantation of an alternative industry, was unable to offer the migrantssufficient 'work places'. In this way, the 'marginal crowd' began to settle down in the suburbs of the city. This study, in the context of the object theme, analyses two main questions related to the reality 'WOlLQ' and to the economic exploitation forms: ~) the relations of production in the economic regime of subsistence and in the capitalist regime of industrial production with the consequent 'positions' of the workman in the productive processj ~~) the deriving educative effects of the productive process, either in the economic regime of subsistence, or in the capitalist industrial regime. The two questions are theoretically debated andconfro~ ted with the proposed reality, giving origin to conclusions that, in a general formulation, can be summarized as follows: a) the caboclos of the highland region of Santa Catari na, when under an economic regime of subsistence, held in fee the productive processj there was a social division of the work and aclimate of freedom which made possible the development of knowledge from their life and work experience, the production of most of their tools, and the making of necessary manufactures adapted to their own surrounding ditionsi -- - --- other con- ------ b) however, these same caboclos, when absorbed by the capitalist industrial process of production - tipified by the work in saw-mills - lost the control of the productive processj this was caused by the technologic division of the work, since each man began to perform a dull and repeti tive action, directed by the speed of the 'major-saw' j man resigned form his skill and inventive power and surrendered to an executive authority which turned him into a 'collective worker'j the new productive process, besides rnaking each rnan a copy of a pattern, put the caboclos in a situation in which the daily work experiencedidn't add anything in terrns of autogenesis of knowledgei and even the environrnental educative rneans were reduced to new forrns of adaptation to the productive process, relegating rnan's inventive power to inertia.